Implementation of Electronic Word of Mouth at Communication and Informatics Institutions of Central Lombok Regency to Execute Public Internet Program - Aqila, Firyal; Ardia, Velda (PT Literasi Nusantara Publisher, 2023)
Diskominfo Central Lombok is a Government Agency that has the main task of serving the community in sharing communication and information. The research entitled